Artificial pollination apparatus (2013)
PURPOSE: An artificial pollination apparatus is provided to improve workability and to save a pollination solution by spaying the pollination solution only onto a stigma. CONSTITUTION: An artificial pollination apparatus comprises a storage tank(20) for storing a pollination solution; an injection part(30) with an injection nozzle(34) for spraying the pollination solution; a high pressure supply unit which sprays the pollination solution from the injection nozzle to the outside at a predetermined pressure; a sensor unit(40) which measures the distance between the injection nozzle and a pollination subject; and a controller(50) which controls the operation of the high pressure supply unit according to the distance.